2010
DOI: 10.1248/bpb.33.111
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Intestinal Permeability and First-Pass Metabolism of Drugs in Cynomolgus Monkeys Using Single-Pass Intestinal Perfusion

Abstract: where Fa is the fraction of dose absorbed from the gastrointestinal (GI) tract, Fg is the intestinal availability, that correspondent to the fraction of dose not metabolized in the intestinal wall during the absorption process and Fh is the fraction of dose not metabolized in the liver before reaching the systemic circulation. Therefore, the values of (1ϪFg) and (1ϪFh) mean the first-pass metabolism of orally administered drugs in GI tract and the liver, respectively. In order to select the appropriate candida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Albrecht et al (1999) reported that 24-28-year old and 67-81-year old men did not differ in a majority of pharmacokinetic parameters, but midazolam was distributed more slowly in aged men. Intestinal metabolism of oral midazolam is greater in cynomolgus monkeys compared to humans (Takahashi et al 2010), suggesting that humans may be more sensitive to midazolam compared to monkeys. However, both cynomolgus monkeys (Kanazu et al 2004) and humans (Thummel and Wilkinson 1998) metabolize midazolam via cytochrome P450 3A enzymes, with no difference between young and aged adult humans (Klotz 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Albrecht et al (1999) reported that 24-28-year old and 67-81-year old men did not differ in a majority of pharmacokinetic parameters, but midazolam was distributed more slowly in aged men. Intestinal metabolism of oral midazolam is greater in cynomolgus monkeys compared to humans (Takahashi et al 2010), suggesting that humans may be more sensitive to midazolam compared to monkeys. However, both cynomolgus monkeys (Kanazu et al 2004) and humans (Thummel and Wilkinson 1998) metabolize midazolam via cytochrome P450 3A enzymes, with no difference between young and aged adult humans (Klotz 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the interactions between the intestine and liver units in a single context contributed to an innovative attempt to approach and integrate ADME parameters (such as drug availability) in the same in vitro-in silico framework. Human paracetamol availability, F, has been reported as 0.88 (Takahashi et al, 2009(Takahashi et al, , 2010 whereas we estimated a value ranging between 0.24 and 0.41 using the parallel tube liver model and the gut model. (Mahler et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of the bioavailability of a β-glucuronidase inhibitor in mice before and after pretreatment with 1-ABT established that its low bioavailability (21%) was due to first pass metabolism [ 107 ]. An investigation of intestinal permeability and first-pass metabolism of acetaminophen, verapamil, and midazolam using single-pass intestinal perfusion showed that 1-ABT increased the intestinal availability of these three drugs to 0.8–0.85 in cyanomologous monkeys, confirming that they are extensively metabolized in the intestine [ 108 ]. A significant increase in the exposure of mice to midazolam was observed when the mice were pretreated with 1-ABT [ 109 ].…”
Section: Analogues Of 1-abtmentioning
confidence: 99%